Traditional Machismo, Caballerismo, and the Pre-Exposure Prophylaxis (PrEP) Cascade Among a Sample of Latino Sexual Minority Men. Issue 1 (2nd January 2021) - Rivera, David B.; Brady, John P.; Blashill, Aaron J.
ABSTRACT: Between 2010 and 2017, HIV diagnoses increased 17% among Latino sexual minority men (SMM) while decreasing 19% among White SMM and stabilizing among African American SMM. Traditional machismo is characterized by aggressiveness/power; caballerismo consists of family values/chivalry. Latino SMM high in traditional machismo may avoid seeking Pre-Exposure Prophylaxis (PrEP) to prevent being stigmatized as effeminate. Latino SMM high in caballerismo may be more likely to use PrEP to remain healthy for their family and/or partners. The current study explored the association between traditional machismo and caballerismo with four steps of the PrEP cascade. Participants were 151 HIV-negative/unknown Latino SMM living in San Diego, California ( M = 24.18 years old) who completed an online study. Traditional machismo was associated with low odds of PrEP awareness, willingness, and adherence and high odds of PrEP use. Caballerismo was associated with greater odds of PrEP awareness, willingness, use, and adherence. High levels of traditional machismo among Latino SMM may be a barrier to PrEP. Caballerismo may be a facilitator of PrEP awareness, willingness, use, and adherence. Programs which serve to move Latino SMM through the PrEP cascade may benefit from discussing culturally-relevant masculinity given the potential for their differential associations with PrEP variables.